Marx's revenge : the resurgence of capitalism and the death of statist socialism - Desai, Meghnad (Verso, 2004)
"This book is intended to annoy and provoke..." A distinguished economist, and a seasoned heretic, Meghnad Desai has spent most of his like as an advocate of the Left. This book is the culmination of a period of reassessment, initiated by the challenge of Thatcherism, the collapse of the Soviet system, and the British Labour Party's Embrace of market-driven politics, which has led Desai to his recognition of 'the end of the road for democratic socialism'.